Protective Effect of Curcumin against the Liver Toxicity Caused by Propanil in Rats. (29th October 2014) - Otuechere, Chiagoziem A.; Abarikwu, Sunny O.; Olateju, Victoria I.; Animashaun, Azeezat L.; Kale, Oluwafemi E.
Abstract : We investigated the protective effects of curcumin on propanil-induced alterations in biochemical indices in blood and liver of male Wistar rats. The study consisted of four treatment groups, with six animals each, designated as control, propanil (20mg/kg), curcumin(50 mg/kg), and curcumin (50 mg/kg) + propanil (20 mg/kg). Rats were administered their respective doses orally, every other day, for 28 days. Propanil administration elicited significant (P < 0.001 ) increases in plasma aspartate aminotransferase and alkaline phosphatase activities, by 24% and 56%, respectively, compared to the control. Treatment with propanil elevated bilirubin, creatinine, and total cholesterol levels in rats, but these were not significant relative to controls. Administration of propanil to rats significantly (P < 0.001 ) increased lipid peroxidation levels. However, catalase activity, vitamin C, and reduced glutathione levels were significantly reduced. Exposure to propanil did not produce any significant changes in packed cell volume, neutrophils, and leukocyte counts. The supplementation of curcumin attenuated the adverse effects of propanil intoxication by reducing lipid peroxidation levels and restored the levels of serum enzymes and reduced glutathione. The present study showed that propanil increased oxidative stress and altered some biochemical parameters in the rats but curcumin could afford some protection to attenuate propanil-induced toxicity in the liver.